FACTORING- CREDIT OPPORTUNITIES IN ROMANIA - ADELA IONESCU (Challenges of the Knowledge Society)
Capital is the main factor of production, business development becomes virtually impossible without taking into account the financial market and the resources it provides to businesses. Any business, regardless of its degree of development, is involving direct contact with financial markets, namely the institutions that mediate mobilization of capital and the services they provide. Understanding the functioning of the financial system, the specific financial mechanisms through which savings are allocated to support capital investments and the costs and risks involved is essential for the development of a solid base for business. In this context, factoring operations can support economic agents, allowing a transfer of commercial receivables from their holder to a factor who commits to their recovery and guarantee such operations even if temporary or permanent insolvency of the debtor . Thus, factoring is a complex technique in at least two aspects, of the debt and the transfer of credit. . Factoring is a means of financing business, especially export-import transactions, less known in Romania. Maybe because of poor business environment popularize the term is as little known as it was a few years ago the leasing. Present in Romanian legislation since 2002, factoring appears as a contract between one party (called adherent), providing goods or service and a banking company or a financial institution specialized (called factor), which the last one shall finance debts pursuing and preservation against credit risks and adherent gives factor by way of sale, debts arising from the sale of goods or services to third parties. The article is divided into three parts. In the first part we defined the concept of factoring and international factoring, then I presented the advantages and development of factoring in Romania, and the last part conclusions.